2013
DOI: 10.1016/j.jvs.2013.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Design considerations for studies of the biomechanical environment of the femoropopliteal arteries

Abstract: A review of the current literature reveals heterogeneous study designs that confound interpretation. Studies included different physiologic settings from young to mature participants, participants with and without disease, and cadavers. Investigators used a range of imaging modalities and definitions of arterial segments, which affected our ability to compile the data as we learned that deformations vary according to the specific anatomic location within the SFA/PA. As a result of this analysis, we identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
5
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 23 publications
(30 reference statements)
3
72
5
7
Order By: Relevance
“…because the SFA and PA that comprise the FPA segment, undergo large deformations during flexion of the limb [9,14]. These severe deformations are reflected clinically by the frequency of disease development and the high incidence of stent fractures [2,31 -33], and are believed to contribute to poor clinical outcomes of current open and endovascular PAD treatments [9]. Torsion is one of the main deformation modes, but is also the most challenging to measure in vivo due to lack of identifiable arterial markers that can be tracked with limb flexion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…because the SFA and PA that comprise the FPA segment, undergo large deformations during flexion of the limb [9,14]. These severe deformations are reflected clinically by the frequency of disease development and the high incidence of stent fractures [2,31 -33], and are believed to contribute to poor clinical outcomes of current open and endovascular PAD treatments [9]. Torsion is one of the main deformation modes, but is also the most challenging to measure in vivo due to lack of identifiable arterial markers that can be tracked with limb flexion.…”
Section: Discussionmentioning
confidence: 99%
“…A major difference between the FPA and other arterial segments are the large deformations experienced by the SFA and PA during flexion of the limbs. These deformations are particularly important for the design of FPA stents, as the inability of certain stent designs to accommodate these severe deformations during locomotion may result in arterial wall injury, poor device apposition and even fracture of the stent [9]. All these can lead to deleterious cellular and biochemical responses, culminating in restenosis and reconstruction failure [2,[10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…De-spite that stent implants are efficient in restoring normal blood flow over time new blockage can form called restenosis [1]. Research studies based on clinical data have concluded that in addition to stent design, the geometry of the artery can contribute to the development of restenosis [4,21,22]. For example several conditions such as twisting, compression, elongation and flexion as shown in Figure 3 can be noted for artery.…”
Section: J Biomed Eng Res 2016 | Vol 1: 102 Jscholar Publishersmentioning
confidence: 99%
“…The possibilities of Finite Element Analysis (FEA) and Computational Fluid Dynamics (CFD), combined with contemporary imaging techniques, greatly facilitate stent research. Tremendous amount of research has been done on coronary artery stenting, on stent geometry, and on estimating artery-stent interaction however, very little is reported on superficial artery stenting and the process of using real artery geometry from patient data for the computational models [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation